Arbuscular mycorrhizal fungi and coconut coir dust application enhance the production of foliar secondary metabolites in Passiflora cincinnata Mast. seedlings. Issue 5 (27th April 2022) - Falcão, Eduarda Lins; da Silva, Fábio Sérgio Barbosa
Abstract: Background: Passiflora cincinnata Mast. is used in family farming due to its easy cultivation and pathogens resistance. Moreover, in its leaves are produced secondary metabolites that confer anxiolytic properties to the species. However, these biomolecules are produced at low concentrations, making it necessary to search for alternatives that increase the production of these compounds, such as the application of arbuscular mycorrhizal fungi and coconut coir dust in the cultivation substrate. This study aimed to select the efficient AMF and coir dust proportion in enhancing the production of foliar metabolites in P. cincinnata. Results: Plants cultivated in substrates with one‐third coconut coir dust and inoculated with Acaulospora longula Spain and N.C. Schenck concentrated more total phenols (91.39%), total tannins (147.47%), and total saponins (151.41%) in comparison to non‐inoculated seedlings. Furthermore, seedlings inoculated with A. longula and grown without coconut coir dust produced more flavonoids than the other treatments. Conclusion: The combined application of AMF and one‐third of coir dust is an option to optimize the production of metabolites of interest in P. cincinnata, constituting an alternative for phytomass supply to the anxiolytic herbal medicines industries based on Passiflora .